2018
DOI: 10.1111/cge.13168
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Huntington disease in Cyprus: A 20‐year retrospective study

Abstract: Huntington disease (HD) is most prevalent among populations of western European descent and isolated populations where founder effects may operate. The aim of this study was to examine the epidemiology of HD in Cyprus, an island in southern Europe with extensive western European colonization in the past. All registered HD patients in the Cyprus, since 1994, were included. Detailed pedigrees and clinical information were recorded and maps, showing the geographic distribution of HD, were constructed. Requests fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…These estimates are within the contemporary European range [3,34] and in concordance with our general population CAG repeat length distribution (data not shown). Prevalence, however, is lower than that reported in the United Kingdom [7] or Ireland [35], higher than in some northern European countries like Finland [36] or Iceland [37], and in line with other southern European populations [38][39][40][41]. Other post molecular studies carried out in Spain have also reported comparable HD prevalence figures (4.6 and 4.0, per 100,000 in Asturias and Murcia, respectively [42,43]; in contrast, lower prevalence was observed for Balearic Islands (2 per 100,000) [43].…”
Section: Discussionsupporting
confidence: 64%
“…These estimates are within the contemporary European range [3,34] and in concordance with our general population CAG repeat length distribution (data not shown). Prevalence, however, is lower than that reported in the United Kingdom [7] or Ireland [35], higher than in some northern European countries like Finland [36] or Iceland [37], and in line with other southern European populations [38][39][40][41]. Other post molecular studies carried out in Spain have also reported comparable HD prevalence figures (4.6 and 4.0, per 100,000 in Asturias and Murcia, respectively [42,43]; in contrast, lower prevalence was observed for Balearic Islands (2 per 100,000) [43].…”
Section: Discussionsupporting
confidence: 64%
“…This renders genetic studies in the Cypriot population informative for the genetically similar populations as well. Characteristic of the genetic admixture and of the peculiarity of the Cypriot population are the geographical clusters of other neurological genetic diseases such as Friedreich ataxia, Huntington disease, and Familial Amyloid Polyneuropathy (13–15). Therefore, the investigation of the epidemiology of other neurological diseases such as PD in the Cypriot population is of particular interest.…”
Section: Introductionmentioning
confidence: 99%
“…In other European countries, the incidence rates calculated were the following, all of them per 100.000 person-years: 0.3 in the province of Ferrara, northern Italy (1990-2009) [18]; 1.8 in Germany (2015-2016) [19]; 0.14 in Iceland (1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007) [20]; the minimum incidence rate was 0.22, being able to reach 0.44 in Greece (1995Greece ( -2008 [21]; 0.25 in Cyprus (1984-2015) [22]; and 0,72 in United Kingdom (1990-2010) [23]. So, the incidence of HD varies from 0.14 to 1.8 per 100.000 person-years in Europe.…”
Section: Discussionmentioning
confidence: 93%